Shift 4.2 units to the left: Add 4.2 to the input x:
\(\displaystyle{y}={\left({x}+{4.2}\right)}^{{{3}}}\)

Reflect across the yy-axis: Change the sign of x: \(\displaystyle{y}={\left(−{x}+{4.2}\right)}^{{{3}}}\)

Shift upward 2.3 units: Add 2.3 to the output: \(\displaystyle{y}={\left(−{x}+{4.2}\right)}^{{{3}+{2.3}}}\)

Reflect across the yy-axis: Change the sign of x: \(\displaystyle{y}={\left(−{x}+{4.2}\right)}^{{{3}}}\)

Shift upward 2.3 units: Add 2.3 to the output: \(\displaystyle{y}={\left(−{x}+{4.2}\right)}^{{{3}+{2.3}}}\)